Pottery Production, Landscape and Economy of Roman Dalmatia Interdisciplinary Approaches. - Lipovac Vrkljan, Goranka (Archaeopress Roman Archaeology Ser., 2018)
This book presents interdisciplinary research carried out on the Roman sites of pottery workshops active within the coastal area of the province of Dalmatia as well as on material recovered during the excavations.